Comparative Analysis of miRNAs and Their Target Transcripts between a Spontaneous Late-Ripening Sweet Orange Mutant and Its Wild-Type Using Small RNA and Degradome Sequencing - Wu, Juxun; Zheng, Saisai; Feng, Guizhi; Yi, Hualin (Frontiers in Plant Science, 2016)
Fruit ripening in citrus is not well understood at the molecular level. Knowledge of the regulatory mechanism of citrus fruit ripening at the post-transcriptional level in particular is lacking. Here, we comparatively analyzed the miRNAs and their targeted genes in a spontaneous late-ripening mutant, ‘Fengwan’ sweet orange (MT) (Citrus sinensis L. Osbeck), and its wild-type counterpart ('Fengjie 72-1', WT). Using high-throughput sequencing of small RNAs and RNA degradome tags, we identified 107 known and 21 novel miRNAs, as well as 225 target genes. A total of 24 miRNAs (16 known miRNAs and 8 novel miRNAs) were shown to be differentially expressed between MT and WT. The expression pattern of several key miRNAs and their target genes during citrus fruit development and ripening stages was examined. Csi-miR156k, csi-miR159 and csi-miR166d suppressed specific transcription factors (GAMYBs, SPLs and ATHBs) that are supposed to be important regulators involved in citrus fruit development and ripening. In the present study, miRNA-mediated silencing of target genes was found under complicated and sensitive regulation in citrus fruit. The identification of miRNAs and their target genes provide new clues for future investigation of mechanisms that regulate citrus fruit ripening.